Liability of the Carrier for the loss of the Delivery (Studi Kasus CV. Maju Berkah Tanjung Transport) - Selvi Apria; Nurhilmiyah Nurhilmiyah (LEGAL BRIEF, 2024)
This research is motivated by the phenomenon of the loss of consignments experienced by CV Maju Berkah Tanjung Transport as a goods transportation service company. The research aims to describe the causal factors, the concept of responsibility, and the obstacles in resolving cases of loss of consignments. The research method used in this research is sociological/empirical legal research or other terms used are sociological legal research and can also be called field research conducted through interviews with CV employees. Maju Berkah Tanjung Transport and document studies related to cases of lost shipments over the past year. The results show that the main causal factors are human negligence in the company's operational system and criminal acts. The concept of responsibility is based on the transport agreement and insurance contract to ensure certainty of compensation for customers and financial protection of the company. There are several obstacles in the claims process such as lack of valid evidence, excessive consumer demands, and indications of claim fraud. In conclusion, effective risk management and claims handling are essential to ensure that cases of lost goods are resolved without harming all parties concerned.